Removal Of Lead (Pb2+) From Aqueous Solutions By Natural Bentonite - Wahyu Wilopo; Doni Prakasa Eka Putra; I Wayan Warmada; Tsuyoshi Hirajima (Journal of Applied Geology, 2015)
The aim of the present work is to investigate the ability of natural bentonite (untreated) from Pacitan, East Java to remove lead ions from aqueous solution. The bentonite has specific surface area and cation exchange capacity of 27.52 m2 g−1 and 65.20 meq/100 gr of bentonite, respectively. Towards this aim, batch adsorption experiments were carried out and the effect of various parameters on this removal process has been investigated. The effects of pH, grain size of bentonite, adsorption time and lead ion concentration on the adsorption process were examined. The optimum pH for adsorption was found to be 9, with the finer grain size of bentonite is more effective. In adsorption studies, residual lead ions concentration reached equilibrium in a duration of 24 hours. Adsorption of lead on bentonite appeared to follow Freundlich isotherm. Our results demonstrate that the adsorption process was mostly dominated by ion exchange process. Keywords: Removal, lead, aqueous solution, natural bentonite, adsorption.